Neuronal Nitric Oxide Synthase in Vascular Physiology and Diseases - Costa, Eduardo D.; Rezende, Bruno A.; Cortes, Steyner F.; Lemos, Virginia S. (Frontiers in Physiology, 2016)
The family of nitric oxide synthases (NOS) has significant importance in various physiological mechanisms and is also involved in many pathological processes. Three NOS isoforms have been identified: neuronal NOS (nNOS or NOS 1), endothelial NOS (eNOS or NOS 3), and an inducible NOS (iNOS or NOS 2). Both nNOS and eNOS are constitutively expressed. Classically, eNOS is considered the main isoform involved in the control of the vascular function. However, more recent studies have shown that nNOS is present in the vascular endothelium and importantly contributes to the maintenance of the homeostasis of the cardiovascular system. In physiological conditions, besides nitric oxide (NO), nNOS also produces hydrogen peroxide (H2O2) and superoxide (O2•-) considered as key mediators in non-neuronal cells signaling. This mini-review highlights recent scientific releases on the role of nNOS in vascular homeostasis and cardiovascular disorders such as hypertension and atherosclerosis.